Utilizing the Bioactivity of Nutmeg Leaf Oil to Raise the Natural Antioxidant Content of Cooking Oil - Azwar Azwar; Syaubari Syaubari; Ahmad Khairi Abdul; Aswin Siswanto; Revanza Bariqzi; Jakfar Jakfar; Farid Mulana; Hisbullah Hisbullah (Jurnal Serambi Engineering, 2022)
Nutmeg oil, also known as essential oil, is an oil extracted from the seeds or leaves of nutmeg through a distillation process. Nutmeg oil has several advantages, including as an antibacterial ingredient, an additive in the perfume industry, and as a raw material for medicines in the pharmaceutical industry. In this study, the essential oil from nutmeg leaves was produced using the steam-water distillation method, where the nutmeg leaves were dried before the steam-water distillation process was carried out. As a fixed variable, 150 g of bulk cooking oil and 150 g of bimoli cooking oil were used, while as a variable, steam-water distillation temperature was used with temperature variations of 105 oC, 115 oC, and 125 oC. Samples of 1 mL, 2 mL, 3 mL, and 4 mL of nutmeg leaf oil were mixed with bulk cooking oil to compare the free fatty acid oxidation ability and peroxide value after 1 day, 3 days, 5 days, and 7 days. Analysis of the compound content of nutmeg leaf oil, free fatty acids, peroxide number, and antioxidant activity was carried out using GC-MS and 0.004% DPPH. The production of nutmeg leaf oil was obtained as much as 91 ml by steam distillation at a maximum temperature of 125 oC. Using a DPPH of 0.004 percent and a quantitative measure of IC50, the optimal antioxidant activity at 125 oC was found to be 2.03 percent. A comparison of free fatty acid numbers and peroxide values found in this study revealed that pure bimoli cooking oil had the lowest free fatty acid and peroxide values.